Oil price movements and the global economy: A model-based assessment - Selim Elekdag; René Lalonde; Douglas Laxton; Dirk Muir; Paolo Pesenti (Bank of Canada, 2007)
We develop a five-region version (Canada, an oil exporter, the United States, emerging Asia and Japan plus the euro area) of the Global Economy Model (GEM) encompassing production and trade of crude oil, and use it to study the international transmission mechanism of shocks that drive oil prices. In the presence of real adjustment costs that reduce the short- and medium-term responses of oil supply and demand, our simulations can account for large endogenous variations of oil prices with large effects on the terms of trade of oil-exporting versus oil-importing countries (in particular, emerging Asia), and result in significant wealth transfers between regions. This is especially true when we consider a sustained increase in productivity growth or a shift in production technology towards more capital- (and hence oil-) intensive goods in regions such as emerging Asia. In addition, we study the implications of higher taxes on gasoline that are used to reduce taxes on labor income, showing that such a policy could increase world productive capacity while being consistent with a reduction in oil consumption.
Keywords: E66; F32; F47; 330; Economic models; Inflation and prices; International topics; Erdölförderung; Schock; Ölpreis; Terms of Trade; Inflationsrate; Wohlfahrtseffekt; Mehr-Länder-Modell; Welt